2016
DOI: 10.6023/cjoc201510008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical and Electrochemical Properties of 10-Methyl-10H-phenothiazine-5,5-dioxide Derivatives

Abstract: Based on 10-methyl-10H-phenothiazine-5,5-dioxide unit as an acceptor and 9,10-dihydro-9,9-dimethyl-acridine (DMAC) or phenoxazine (PXZ) as donors, four intramolecular charge transfer (ICT) compounds were designed and synthesized by Buchwald-Hartwig cross coupling reactions. Their ground-state geometries were optimized with density functional theory (DFT) at B3LYP level and vertical transition energies were calculated using the optimal Hartree-Fock (HF) exchange method. Resulting compounds were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The Suh group [18] reported that the EQE of the prepared device of the bipolar host material N -(3,5-di(9 H -carbazol-9-yl)phenyl)- N -(pyridin-2-yl)pyridin-2-amine (DCPPy) based on carbazole group is 21.6%. The Wang group [19] designed a host material with symmetrical structure based on phenothiazine-5,5-dioxide. But the host materials with asymmetric structure based on the phenothiazine-5,5-dioxide were rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The Suh group [18] reported that the EQE of the prepared device of the bipolar host material N -(3,5-di(9 H -carbazol-9-yl)phenyl)- N -(pyridin-2-yl)pyridin-2-amine (DCPPy) based on carbazole group is 21.6%. The Wang group [19] designed a host material with symmetrical structure based on phenothiazine-5,5-dioxide. But the host materials with asymmetric structure based on the phenothiazine-5,5-dioxide were rarely reported.…”
Section: Introductionmentioning
confidence: 99%